Antiviral activity of berberine - Warowicka, Alicja; Nawrot, Robert; Goździcka-Józefiak, Anna (Archives of virology, 2020)
Plants are a rich source of new antiviral, pharmacologically active agents. The naturally occurring plant alkaloid berberine (BBR) is one of the phytochemicals with a broad range of biological activity, including anticancer, anti-inflammatory and antiviral activity. BBR targets different steps in the viral life cycle and is thus a good candidate for use in novel antiviral drugs and therapies. It has been shown that BBR reduces virus replication and targets specific interactions between the virus and its host. BBR intercalates into DNA and inhibits DNA synthesis and reverse transcriptase activity. It inhibits replication of herpes simplex virus (HSV), human cytomegalovirus (HCMV), human papillomavirus (HPV), and human immunodeficiency virus (HIV). This isoquinoline alkaloid has the ability to regulate the MEK-ERK, AMPK/mTOR, and NF-κB signaling pathways, which are necessary for viral replication. Furthermore, it has been reported that BBR supports the host immune response, thus leading to viral clearance. In this short review, we focus on the most recent studies on the antiviral properties of berberine and its derivatives, which might be promising agents to be considered in future studies in the fight against the current pandemic SARS-CoV-2, the virus that causes COVID-19.